The African American Dementia and Aging Project: an Oregon-based longitudinal study - Lindauer, Allison; Croff, Raina; Duff, Kevin; Mattek, Nora; Fuller, Patrice; Pierce, Aimee; Bonds Johnson, Kalisha; Kaye, Jeffrey (Frontiers in Dementia, 2024)
Introduction. The vast majority of studies on aging, cognition, and dementia focus on non-Hispanic white subjects. This paper adds to the extant literature by providing insight into the African American aging experience. Here we describe the study design and baseline characteristics of the African American Dementia and Aging Project (AADAPt) study, which is exploring aging and cognition in African American older adults in Oregon.Methods. African American older adults (n=177) participated in AADAPt, a longitudinal study that collected data on cognitive, physical, and social functioning in annual visits since 2000.Results. AADAPt participants had risk factors for developing dementia in future, such as hypertension and hyperlipidemia, but also reported protective factors such as high social engagement.Americans that includes data on cognition, social engagement, and physical health, which are crucial for understanding the experience of under-represented groups and making future studies more inclusive.